A defeat to reckon with: On Scotland, economic competence, and the complexities of Labour's losses. Issue 1 (June 2015) - Curtice, John
<x xml:space="preserve">Abstract</x> There is no single straightforward explanation for Labour's election losses, either in Scotland or in Britain as a whole. But to win a fresh hearing among key demographics, writes John Curtice, the party must convince voters that it can create a better and more appealing economy, not just competently steward it.